INTERKALASI BENZALKONIUM KLORIDA KE DALAM MONTMORILLONIT TERAKTIVASI ASAM DAN PEMANFAATANNYA UNTUK MENINGKATKAN KUALITAS MINYAK DAUN CENGKEH - Suarya, P. (Jurnal Kimia (Journal of Chemistry); Vol. 3, No. 1 Januari 2009)
This research was conducted to observe the surfactant intercalation into acid-activated montmorillonite clay. This clay was applied as adsorbent for increasing the quality of clove leaf oil. The acid used as an activation was 1.5 M sulphuric acid and the surfactant for intercalation was Benzalkonium Chloride (BKC) with concentration variation (0; 0.1; 0.5; 1; and 2%). The result of the reseach showed that the changes of basal spacing d001 for S0-0; Sa-0; Sa-0,1; Sa-0,5; Sa-1; and Sa-2 were 15.15548; 15.40269; 15.20580; 14.62099; 14.77594; and 14.74415 Å respectively. The surface area for S0-0; Sa-0; Sa-0,1; Sa-0,5; Sa-1; and Sa-2 were 26.2239; 27.4035; 26.0482; 26.4557; 27.7885; and 26.6809 m2/g respectively. The Sa-0,1 adsorbent had the highest surface acidity (1.0135 ± 0.01100 mmol/g). Every gram of adsorbent Sa-0,1 had the highest adsorption capacity to clarify 20.0 mL clove leaf oil at 120 minutes contact time. After adsorption by Sa-0,1 the clove leaf oil was clearer and contained higher concentration of eugenol than before adsorption.
Keywords: montmorillonite clay, acid-activated, surfactant benzalkonium chloride, clove leaf oil